PERAN LINGKUNGAN KELUARGA DALAM KEGIATAN BERMAIN ANAK USIA DINI DIMASA PENDEMI COVID-19 - Oktaviana, Anita; Munastiwi, Erni (Jurnal Golden Age, 2021)
Early childhood generally spends more time playing together with their peers, so that the lack of time for children to play activities in the family environment, this will have an impact on the interaction between children and the family environment. This study aims to describe the role of the family in children's play activities during the COVID-19 pandemic, during the pandemic the family environment plays a very important role in the child's development process, such as creating a comfortable atmosphere and making various playing media that attract children's interest. This type of research is field research using a qualitative approach. The data in this study were obtained through observation, interviews, and documentation. In analyzing the data, the researcher used three stages, namely reduction, data presentation, and drawing conclusions. Based on the results of this study, it can be seen that the family environment has a very important role in the process of child development, one of which is through play activities, especially in providing or facilitating all the needs of children when playing activities take place.